Surgical reconstruction of the anterolateral acromion with a tricortical iliac crest bone graft after extensive acromioplasty - Nolte, Anna-Katharina; Nolte, Philip-Christian; Loew, Markus; Schnetzke, Marc; Lichtenberg, Sven (Obere Extremität, 2021)
Subacromial decompression is one of the most frequently performed procedures in the setting of arthroscopic shoulder surgery and typically includes acromioplasty. However, the indication for acromioplasty remains a subject of debate. Possible complications involve deltoid muscle insufficiency due to an excessive removal of the anterior acromion. This case report is intended to draw attention to this particular complication and its management.